Does water addition during the industrial milling phase affect the chemical-sensory quality of olive oils? The case of cv. Arbequina oils. Issue 17 (30th November 2022) - Marx, Ítala M.G.; Casal, Susana; Rodrigues, Nuno; Cruz, Rebeca; Veloso, Ana C.A.; Pereira, José A.; Peres, António M.
Graphical abstract: Highlights: Olive oils extracted at industry without or with water addition during milling step. All cv . Arbequina oils classified as extra virgin olive oil. Extraction without water addition increased ripe fruity sensation. Extraction without usual water addition increased the secoiridoids contents. Water addition level influenced oils composition allowing E-tongue discrimination. Abstract: At olive oil industrial extraction, water addition is a practice overcoming the formation of thick pastes. The effect of water addition (0 to 6.2%, kgadded water /kgolives ), during the industrial milling of cv . Arbequina olives, on the oils' chemical-sensory quality, was evaluated. Despite the extra virgin olive oil classification, compared with the water incorporation (1.2–6.2%), extraction without water addition resulted into oils that showed less primary oxidation (lower peroxide values and K 232 ), greater total phenolic content (+12–22%) and higher oxidative stability (+22–31%). No water addition increased the oils secoiridoids content (+5–13%), mainly oleacein (+27–79%). Oils extracted without water addition had a more intense ripe fruity sensation (≥ +11%) but lower fruit intensities (at least −4%). Thus, the quality and stability of the cv . Arbequina oils can be favoured if extracted without adding water during the olives industrial milling.